Financial Distress terhadap Manajemen Laba Dengan Mekanisme Corporate Governance sebagai Pemoderasi - Vidia Damayanti; Yeterina Widi Nugrahanti (AFRE (Accounting and Financial Review), 2022)
This study aims to determine the effect of financial distress on earnings management with corporate governance mechanisms as a moderating variable. Earnings management in this study is measured by real earnings management, namely abnormal operating cash flows. The level of financial distress in this study is proxied by leverage. This study uses 135 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 with a total of 405 observations. This study uses Generalized Least Square (GLS) panel data regression. The results showed that financial distress had a positive effect on earnings management as measured by abnormal CFO. This study also found that managerial ownership and institutional ownership weakens the positive influence of financial distress on earnings management as measured by abnormal CFO.DOI: DOI: https://doi.org/10.26905/afr.v5i2.7762